Indikator Kebahagiaan (Al-Sa’adah) dalam Perspektif Alquran dan Hadis - Nanum Sofia; Endah Puspita Sari (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2018)
Happiness is the most essential thing for human life. There are various indicators of happiness, but there are no indicators that use the Islamic perspective. This study aims to examine indicators of happiness (al-sa'adah) in an Islamic perspective that refers to and guided primarily by the Koran and Hadith. This study uses literature studies, by collecting verses from the Koran and Hadith related to the concepts of happiness in Arabic. The researcher found that overall, there are 164 verses from 122 letters of the Koran and 24 theorem of hadiths. Based on the search for arguments and verses related to happiness (al-sa'adah), researchers found 17 indicators of happiness according to the The Qoran and Hadith, namely: Faith and takwa (50 verses), tafaqquh fid-dien (2 verses), pious charity (23 verses), patience (7 verses), thanksgiving (7 verses), tazkiyatun al-nafs (2 verses), amar ma'ruf nahi munkar (3 verses), jihad fi sabilillah (5 verses), seeking and receiving the blessing of Allah (10 verses), dzikr (3 verses), get the gift / mercy from Allah (28 verses), ishlah (7 verses), uswah hasanah (2 verses), seek Allah's protection (2 verses), surrender (3 verses), reject evil with goodness (3 verses) and keeping oral and deeds (5 verses).